2014
DOI: 10.1002/mnfr.201300599
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal C‐terminal maltase‐glucoamylase hydrolyzes large size starch digestion products that may contribute to rapid postprandial glucose generation

Abstract: The findings suggest that partial inhibition of ctMGAM, such as by natural inhibitors found in foods, might be used to moderate the early stage of high glycemic response, as well as to extend digestion distally; thereby having relevance in regulating glucose delivery to the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…These enzymes are located close to the active transport sites for monosaccharides (Eliasson, ). The four enzymes, distinguished by their N‐ and C‐terminal subunits, are ntMGAM (maltase), ctMGAM (glucoamylase), ntSI (isomaltase), and ctSI (sucrase) (Lee et al, ). The functional differences among these enzymes reflect their degree of specificity for a particular substrate or glycosidic linkage (Lee et al, ).…”
Section: Challenges To the Starch Digestion Hypothesis For Amy1 Cnvmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes are located close to the active transport sites for monosaccharides (Eliasson, ). The four enzymes, distinguished by their N‐ and C‐terminal subunits, are ntMGAM (maltase), ctMGAM (glucoamylase), ntSI (isomaltase), and ctSI (sucrase) (Lee et al, ). The functional differences among these enzymes reflect their degree of specificity for a particular substrate or glycosidic linkage (Lee et al, ).…”
Section: Challenges To the Starch Digestion Hypothesis For Amy1 Cnvmentioning
confidence: 99%
“…The four enzymes, distinguished by their N‐ and C‐terminal subunits, are ntMGAM (maltase), ctMGAM (glucoamylase), ntSI (isomaltase), and ctSI (sucrase) (Lee et al, ). The functional differences among these enzymes reflect their degree of specificity for a particular substrate or glycosidic linkage (Lee et al, ). Glucoamylase has high specificity for the α‐1,4 bonds at the nonreducing terminus of unbranched chain glucosyl units; maltase hydrolyzes α −1,4 bonds in both starch oligosaccharides, and disaccharide maltose.…”
Section: Challenges To the Starch Digestion Hypothesis For Amy1 Cnvmentioning
confidence: 99%
See 1 more Smart Citation
“…Nt‐SI (also known as isomaltase) and Ct‐SI (also known as sucrase) can also digest branched glucans and sucrose, respectively. We have shown that α‐glucosidase can directly digest large glucans, such as starch molecules, to glucose, and that Ct‐MGAM alone can quickly release approximately 80% of glucose from gelatinized starch . Each of the α‐glucosidases has special preference in substrate structure and digests starch molecules or α‐amylase hydrolysates differently .…”
Section: Starch Digestive Enzymes In the Young Childmentioning
confidence: 99%
“…Although pancreatic a-amylase is often considered the principal enzyme of starch digestion, SI and MGAM represent the control point for glucose generation. Their activities at the luminal-facing apical membrane of the enterocytes are relevant to glucose control (7). SI contains both a-1,4 and a-1,6 activities necessary to produce glucose from starch digestion, whereas MGAM essentially has only a-1,4 activity.…”
mentioning
confidence: 99%